2022
DOI: 10.1177/08901171221116066
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of a 16-Week Whole Food, High Fiber, Plant Predominant Diet among U.S. Employees

Abstract: Purpose To assess improvements in eating behaviors and health measures among adults participating in a whole food plant predominant diet, Full Plate Living (FPL) program. Design Retrospective, post hoc analysis of self-reported 16-week pre-post participant data obtained over a 3 year program period (2017-19). Setting Wellness offering for employees in Southwest U.S. Subjects Of 6,820 enrollees, 4,477 completed the program, further segmented by generational cohorts. Intervention FPL program materials and weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated that FPL participants had statistically significant improvements in eating behaviors of fiber-rich foods between baseline and follow-up ( 20 ). Unique to this study was the development of a total fiber composite.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies demonstrated that FPL participants had statistically significant improvements in eating behaviors of fiber-rich foods between baseline and follow-up ( 20 ). Unique to this study was the development of a total fiber composite.…”
Section: Resultsmentioning
confidence: 96%
“…The study design, procedures, and intervention have been previously described in detail ( 20 ). The 16-week FPL program consisted of individuals receiving weekly online educational videos, FPL program curriculum materials, and online resources to include recipes and meal planning tips.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations